Institutional and public expenditure review of Ghana's Ministry of Food and Agriculture - Kolavalli, Shashidhara; Birner, Regina; Benin, Samuel; Horowitz, Leah; Babu, Suresh Chandra; Asenso-Okyere, Kwadwo; Thompson, Nii Moi; Poku, John (International Food Policy Research Institute, 2010)
The need for agricultural ministries to have the capacity to develop appropriate policies and effectively implement them is becoming increasingly important as African countries, following on their commitment to Comprehensive Africa Agriculture Development Program (CAADP), pursue economic growth through agriculture-led development. The ministries need to take the lead in pulling together evidence based strategies and building partnerships that ensures their ownership. As donors begin to align their policies with those of governments, an increasingly large share of external support to agriculture is likely to be delivered in the form of support to budgets rather than specially implemented projects. Capacities of ministries and effectiveness public systems will have significant bearing on effectiveness and impact of investments in agriculture. This public expenditure and institutional review of Ghana's Ministry of Food and Agriculture offers insights on diagnosing limitations to and identifying strategies for improving the capacity of ministries to make effective use of human and financial resources. The review makes use a conceptual framework in which mission and functions, organizational capacity - a combination of structures, processes and resources -and organizational incentives interact to produce organizational performance. Indicative strategies are recommended that the ministry can use to generate discussions internally and developed a set a reforms that are owned. They key message is that to improve performance both capacity and incentives faced by organizations need to be addressed.